Games without rules : the often interrupted history of Afghanistan - Ansary, Mir Tamim (PublicAffairs, 2012)
Five times in the last two centuries, some great power has tried to invade, occupy, or otherwise take control of Afghanistan. And as Tamim Ansary shows in this illuminating history, every intervention has come to grief for much the same reason: the intervening power has failed to understand that Afghanistan has a story of its own, a story that continues to unfold between--and despite--the interventions. Drawing on his Afghan background, Muslim roots, and Western and Afghan sources, Ansary weaves an epic that moves from a universe of village republics--the old Afghanistan--through a tumultuous drama of tribes. factions, and forces, to the current struggle. Ansary paints a richly textured portrait of a nation that began to form around the same time as the United States but is still struggling to coalesce; a nation driven by its high ambitions but undermined by its own demons, while every forty to sixty years a great power crashes in and disrupts whatever progress has been made.--From publisher description.